Letter from Federico and Annemarie Schnell to Max Bredig, May 4, 1942 - Schnell, Federico (1942)
Federico and Annemarie Schnell write to their friend Max Bredig (1902-1977) to update him on their summer, jobs, child, and correspondence from friends abroad. Fritz writes that he last received a letter from his brother, Alfred (1900-1944), in December, and laments that he is unable to correspond further with him.
Keywords: Schnell, Federico; Bredig, Max Albert, 1902-1977; Schnell, Alfred, 1900-1944